2019
DOI: 10.1080/21645515.2019.1581554
|View full text |Cite
|
Sign up to set email alerts
|

Provider perspectives on multilevel barriers to HPV vaccination

Abstract: Understanding physician recommendation practices for HPV vaccination is a crucial step to developing interventions that can increase high quality recommendations and improve vaccination acceptance. Florida physicians (n = 340) completed a survey assessing recommendation strategies, specifically strength, consistency, and presentation. Physicians were also asked to provide suggestions for improving HPV vaccination in Florida. Responses were dichotomized for each outcome: strength (i.e., strongly recommend vs. o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(14 citation statements)
references
References 27 publications
0
14
0
Order By: Relevance
“…11 The majority of studies have focused on one or two levels of influences (e.g., parents and/or clinicians); however, parents and clinicians have reported that their views on the HPV vaccine are influenced by each other as well as by factors related to the health care system. 6,12,13 Few studies have examined an integrated perspective that includes simultaneously elucidating the processes of care delivery and the role of primary care team members in facilitating the uptake of the HPV vaccine. [14][15][16] The purpose of this study was to examine clinicians, clinic support staff, and parents of adolescent HPV vaccine delivery experiences at the point of care across an integrated primary care network.…”
Section: Introductionmentioning
confidence: 99%
“…11 The majority of studies have focused on one or two levels of influences (e.g., parents and/or clinicians); however, parents and clinicians have reported that their views on the HPV vaccine are influenced by each other as well as by factors related to the health care system. 6,12,13 Few studies have examined an integrated perspective that includes simultaneously elucidating the processes of care delivery and the role of primary care team members in facilitating the uptake of the HPV vaccine. [14][15][16] The purpose of this study was to examine clinicians, clinic support staff, and parents of adolescent HPV vaccine delivery experiences at the point of care across an integrated primary care network.…”
Section: Introductionmentioning
confidence: 99%
“…This includes both clinic-level factors, such as the ability of the clinic to stock the vaccine, the presence of tools like provider prompts and reminder-recall systems and peer influences as well as the characteristics of the broader community in which the provider practices . HCP peers may influence provider attitudes about vaccines or recommendation practices (P. W. Lake et al, 2019a , 2019b ). Providers who were characterized as “Ambivalent HPV recommenders”—those who did not consistently or strongly recommend the HPV vaccine—were also less likely to perceive their peers as thinking the HPV vaccine was important for adolescents or strongly recommending the vaccine (Hopfer et al, 2019 ).…”
Section: A Multilevel Framework For Factors Influencing Provider Reco...mentioning
confidence: 99%
“…Improving reimbursement policies for the HPV vaccine has been associated with an increase in both initiation and completion of the series (Tsai et al, 2018 ). In a study of physicians in Florida, many cited financial barriers such as the high cost of purchasing vaccine or inadequate reimbursement for administered vaccines from insurance companies as primary reasons for not vaccinating patients or referring patients/parents to Departments of Health (P. W. Lake et al, 2019a , 2019b ). However, providers who participated in the Vaccines for Children (VFC), which provides vaccines free of charge to children who are not insured, have Medicaid or whose private insurance does not cover the vaccine, were not only more likely to recommend the HPV vaccine to their patient and/or their parents but also more likely to provide a strong vaccine recommendation (P. W. Lake et al, 2019a , 2019b ).…”
Section: A Multilevel Framework For Factors Influencing Provider Reco...mentioning
confidence: 99%
See 1 more Smart Citation
“…46,47 Two additional papers examine issues of risk compensation post-vaccination in the U.S. and in China, respectively. 48,49 Still other articles involve a latent-class analysis of parental worries, 50 adolescents' perspectives on vaccination, 51 college students' lack of awareness of HPV diseases and vaccination, 52 knowledge and attitudes of caregivers of childhood cancer survivors, 53 HCPs' recommendation profiles and perceptions of barriers to vaccination, 54,55 and perspectives on vaccination among boys in Sweden. 56 Finally, articles in this section apply the Precaution Adoption Process Model to a study of parental vaccine hesitancy, 57 examine preferences for a vaccine-related mobile health tool among young men who have sex with men, 58 and report on the association between vaccination history in women and the HPV vaccine status of their 11-14-y-old children.…”
Section: Hpv Vaccination Policymentioning
confidence: 99%